Nurse Managers' Performance from Nurses' Perspective - MR Mansoorian; M Hosseiny; SH Khosravan (Iran University of Medical Sciences, 2015)
Abstract   Background & Aim: Nurse manager s' efficiency plays an important role in the achievement of health care organizations. This study was carried out with the aim of determining nurse managers' performance in the domains of decision making, planning, direction and evaluation from nurses' perspective in selected educational centers affiliated to Gonabaad University of Medical Sciences.   Material & Method: It was a descriptive, cross-sectional study. A total of 200 nurses were recruited by census. Data was collected by a researcher made questionnaire to evaluate nurse managers' performance in the four domains and analyzed by descriptive statistics and inferential test of Chi square using SPSS-PC (v.20).   Results: The results showed that a small percentage of nurse managers (%5/1) had a very good management performance, 31/9% had a good performance, %50 percent had a poor performance and 13% had a very poor management. The results also showed that nurse managers' performance was poor in the areas of decision making and evaluation, and was good in the domains of planning and guidance from nurses' perspective.   Conclusion: Regarding the findings, empowerment of nurse managers in different levels to improve their performance is needed.